Peran pemeriksaan radiologis: barium enema pada penyakit hirschprung - Novtarina, Rizki (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Hirschprung's Disease (HD) is an aganglionic disease segment of the parasympathetic nerves of Meissner and Auerbach. HD occurs in 1 in 5000 live births. Symptoms include late meconium, green vomiting, and abdominal distension. There are two types of HD short segments and long segments. This transitional zone is usually found in the rectosigmoid region or sigmoid colon, colon descendants, rectum, other colon and can occur in the small intestine. A medium according to type, 75 percent type of long segment, and 15% type of short segment. In the diagnosis, radiological imaging of the barium enema is needed with the position of Anteroposterior-Supine, Semi-Erect, Left Lateral Decubitus. There are seven typical images found (1) Transitional zones, (2) aganglionic segments, (3) Thickening of the mucosal portion of the proximal zone of the zone, (4) Slowing down of barium evacuation, (5) Comparison of rectosigmoid caliber less than 1, (6) Spasms aganglionic area, (7) Image of cobblestone mucosa. Immunohistochemical examination by suction biopsy through taking three places, namely two, three, and five centimeters (cm) from the anal verge.